UPAYA – UPAYA UNTUK MENGIMPLEMENTASIKAN KONVENSI WANITA KE DALAM AWIG- AWIG DESA PAKRAMAN - Sudiana, A.A.Ketut (Jurnal Studi Jender SRIKANDI, 2008)
Access, participation and control for women (krama istri) in pakraman village especially in participating as a decision maker on paruman village applied through revitalizing awig-awig in order to make a responsive gender awig-awig. Furthermore women (karma istri) can be placed in custom sector equally and fairless, in order to achieve the equal position on right and obligation in custom sector on pakraman village, through reinforcement of right equality that regulated on awig-awig based on Women Convention.